Litopedia causando obstrução intestinal em idosa de 71 anos: relato de caso - de Oliveira, Francisco Eliomar Gomes; Santos, Sandra Regina Alves dos; Duarte, Bruno Gomes; Sisnando, Alexandre Sabino (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Ectopic pregnancy is the leading cause of pregnancy-related death during the first trimester, and it occurs in 1 to 2% of pregnancies. Over 90% of ectopic pregnancies are located in the fallopian tube. Abdominal pregnancy refers to an ectopic pregnancy that has implanted in the peritoneal cavity, external to the uterine cavity and fallopian tubes. The estimated incidence is 1 per 10,000 births and 1.4% of ectopic pregnancies. Lithopedion is a rare type of ectopic pregnancy, and it occurs when the fetus from an unrecognized abdominal pregnancy may die and calcify. The resulting “stone baby” may not be detected for decades and may cause a variety of complications. Lithopedion is a very rare event that occurs in 0.0054% of all gestations. About 1.5 to 1.8% of the abdominal babies develop into lithopedion. There are only ∼ 330 known cases of lithopedion in the world. We describe a lithopedion that complicated as intestinal obstruction in a 71-year-old woman.
Keywords: lithopedion; stone baby; ectopic pregnancy; abdominal pregnancy; extrauterine pregnancy